2022
DOI: 10.3390/vaccines10111961
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Produced S1 Subunit Protein of SARS-CoV-2 Elicits Immunogenic Responses in Mice

Abstract: SARS-CoV-2 is responsible for the ongoing COVID-19 pandemic. The virus spreads rapidly with a high transmission rate among humans, and hence virus management has been challenging owing to finding specific therapies or vaccinations. Hence, an effective, low-cost vaccine is urgently required. In this study, the immunogenicity of the plant-produced S1 subunit protein of SARS-CoV-2 was examined in order to assess it as a potential candidate for SARS-CoV-2. The SARS-CoV-2 S1-Fc fusion protein was transiently produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…In this study, we report the first edible COVID-19 tomato vaccine, TOMAVAC, derived by constitutively overexpressing the consensus sequence of the S1 protein of SARS-CoV-2, covering the sequence variation of SARS-CoV-2 spread in Uzbekistan ( 26 ). In contrast, recently, the SARS-CoV-2-S1-Fc fusion protein ( 16 18 ) or a SARS-CoV-2 perfusion spice trimer protein ( 19 ) was transiently expressed in tobacco and harvested for parenteral vaccination studies in animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we report the first edible COVID-19 tomato vaccine, TOMAVAC, derived by constitutively overexpressing the consensus sequence of the S1 protein of SARS-CoV-2, covering the sequence variation of SARS-CoV-2 spread in Uzbekistan ( 26 ). In contrast, recently, the SARS-CoV-2-S1-Fc fusion protein ( 16 18 ) or a SARS-CoV-2 perfusion spice trimer protein ( 19 ) was transiently expressed in tobacco and harvested for parenteral vaccination studies in animals.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor-binding domain (RBD) of the S1 protein was immunogenic and non-allergenic, with very subtle side effects when used as a parenteral protein subunit recombinant vaccine in a previous study ( 28 ). Recent studies ( 16 18 ) reported that the plant-produced S1 subunit protein vaccines against SARS-CoV-2 were immunogenic without any safety concerns in animal experiments. Previous studies also showed that three injections of 10 μg/dose of RBD-specific antigen of S1 protein adequately induced systemic immunity in mice ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A S1 subunit of SARS-CoV-2 fused with the Fc domain was expressed in the N. benthamiana plant using the pBYR2e geminiviral plant expression vector. It was shown that mice immunized with purified S1-Fc protein induced antigen-specific antibodies and T-cell responses in mice ( Panapitakkul et al., 2022 ). The expression level, determined by ELISA to be reported as 30 mg/kg of fresh leaf, seems to be low for commercialization.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most widely used vectors in this approach are RNA viruses, including Tobamoviruses, Potexviruses, Comoviruses and DNA-viruses, e.g., Geminiviruses [ 8 , 9 , 10 , 11 , 12 ]. For example, plant viruses, as an expression system, are used for the generation of individual proteins (antigens) for further use in subunit vaccines (e.g., PA protein of B. anthracis , S1 subunit protein of SARS-CoV-2 [ 13 , 14 , 15 ]).…”
Section: Plant Viruses In Vaccine Manufacturing and Designmentioning
confidence: 99%